The Role of Dopamine Receptors in the Modulation of Mononuclear Phagocytes in Multiple Sclerosis - Lopatina, A. V.; Sviridova, A. A.; Belousova, O. O.; Kuzmina, U. Sh; Melnikov, M. V. (Neuroscience and behavioral physiology, 2025)
Objective . To study the role of D 1 DR and D 2 DR dopamine receptors in the production of interleukins (IL) IL-6 and IL-1β by monocytes and macrophages in patients with relapsing-remitting multiple sclerosis (MS). Materials and methods . Ten patients with relapsing-remitting MS and 10 healthy subjects were investigated. Levels of IL-6 and IL-1β production were assessed in culture supernatants obtained from CD14 + monocytes or macrophages stimulated with interferon-γ (IFN-γ) and lipopolysaccharide (LPS). The role of dopamine receptors in the regulation of CD14 + monocytes and macrophages was studied by incubating cell samples in the presence of specific D 1 DR or D 2 DR antagonists, after which they were stimulated with IFN-γ/LPS. Cytokine levels in cell culture supernatants were measured by enzyme-linked immunosorbent assay. Results . IL-6 and IL-1β production levels by CD14 + monocytes and macrophages were similar in the two groups. Blockade of D 1 DR suppressed cytokine production by both CD14 + monocytes and macrophages in both groups. In contrast, blockade of D 2 DR enhanced cytokine production by CD14 + monocytes and had no effect on macrophages in both groups. Conclusions . Targeting of dopamine receptors may provide an additional mechanism of immunoregulation in MS able to exert both pro- and anti-inflammatory effects on innate immune response cells.